HUBUNGAN KESIAPAN BELAJAR SISWA DENGAN PRESTASI BELAJAR - Mulyani, Dessy (Universitas Negeri Padang, 2013)
Readiness to learn is the most important factor in determining student success in learning. In fact encountered many students have not the readiness to learn like this out in the study, like cheating friend tasks, ofter borrow book friends. The study aims to reveal the relationship readiness to learn of students with learning achievement. Type a descriptive correlational research with findings readiness to learn student quite good, student achievement is quite good, there is a significant relationship between students learning readiness learning achievement.